Relationships between target intraocular pressure and central corneal thickness in stabilized and non-stabilized glaucoma patients (Ukrainian Journal of Ophthalmology, 2025)
Background: Until now, no direct relationship has been established between the target pressure and particular corneal thickness for measurements with different types of tonometers.Purpose: To establish the dependence of target intraocular pressure (IOP) on corneal thickness for Maklakoff applanation tonometry, Pascal dynamic contour tonometry (DCT) and ICare rebound tonometry.Material and Methods: Fifty-two patients (52 eyes; mean age, 71.2 ± 7.7 years) with preoperative cataract underwent an eye examination. These included 13 eyes with cataract associated with stabilized primary open-angle glaucoma (POAG), 20 eyes with cataract associated with non-stabilized POAG, and 19 control eyes with cataract and no history of or present glaucoma. Patients underwent a comprehensive eye examination, Maklakoff applanation tonometry, Pascal dynamic contour tonometry (DCT) and ICare rebound tonometry with IC 200.Results: Group 1 (corneal thickness, 460-489 μm; mean corneal thickness, 479 ± 7.2 μm) patients with stabilized glaucoma had the highest mean values for IOP obtained by any of the three methods at which no glaucoma progression was observed during the most recent 6 months. In group 1 patients with stabilized glaucoma, mean IOP was 16.9 ± 1.2 mmHg for Pascal DCT, 16.2 ± 1.4 mmHg for ICare tonometry, and 20 ± 0.8 mmHg for Maklakoff applanation tonometry. There was a significant difference (р < 0.05) in Maklakoff applanation tonometry IOP, but not in Pascal DCT or ICare tonometry, between group 1 patients with non-stabilized glaucoma (23.8 ± 2.0 mmHg) and those with no glaucoma (16.5 ± 0.7 mmHg). The highest IOP readings were observed in patients of group 5 (corneal thickness, 580–600 μm; mean corneal thickness, 593 ± 4.3 μm) with non-stabilized glaucoma: mean IOP was 28.1 ± 15.0 mmHg for Pascal DCT, 33.2 ± 21.1 mmHg for ICare tonometry, and 25.3 ± 7.5 mmHg for Maklakoff applanation tonometry.Conclusion: Maklakoff tonometry measurements are more sensitive than Pascal DCT or ICare rebound tonometry measurements in patients with thinner corneas. Sensitivity of the tonometry methods under study decreased with increases in corneal thickness and IOP. This should be taking in account while setting a target IOP for glaucoma patients. Among the groups with different corneal thicknesses (groups 1 to 5), group 2 (corneal thickness, 490 – 519 μm) had the highest percentage of patients with non-stabilized glaucoma (75%), followed by group 1 (corneal thickness, 460 – 489 μm; 45.4%).
Keywords: primary open-angle glaucoma; target intraocular pressure; corneal thickness